A Structured Review and Classification of Environmental Pollution Factors at High-Rise Construction Sites - Pham Thi Thanh Nhan,; Nguyen Anh Dung,; Nguyen Minh Ngoc, (International Journal of Sustainable Construction Engineering and Technology, 2026)
Rapid urbanization and the rise of high-rise construction projects have intensified environmental challenges, making pollution control a critical concern for sustainable development. This study aims to systematically identify and classify pollution factors at high-rise construction sites, focusing on the Vietnamese context. A structured literature review was conducted, based on 125 publications retrieved from Web of Science, Scopus, ScienceDirect, and Google Scholar. After screening for relevance and quality, 32 studies were selected for detailed content analysis and frequency analysis of pollution factors. Findings show two categories of factors: direct factors, including construction processes, machinery, equipment, and transportation, and on-site human activities; and indirect factors, encompassing management and people, material management, and environmental and external factors across four pollution categories: air, noise, water and solid waste. A frequency matrix was developed to map how often each factor was linked to different pollution types. Key hotspots identified include material and waste haulage (34.4%), earthworks (31.3%), and machinery operation (31.3%), which collectively dominate air and noise pollution across the reviewed studies. Construction wastewater and runoff (21.9%) are the leading contributors to water pollution. In contrast, design errors (25%) and weak workforce skills (21.9%) were the dominant drivers of solid waste. Based on these results, three strategic directions are proposed: (i) source control and immediate mitigation for mechanized activities and point-source discharges; (ii) upstream prevention through improved design, planning, and material management; and (iii) enhancement of human resources and stakeholder environmental awareness. The study identifies the pollution factors associated with construction activities and emphasizes the necessity for integrated strategies to ensure sustainable urban growth.